KEEFEKTIFAN PEMBELAJARAN MENULIS TEKS BERITA MENGGUNAKAN MODEL 5E LEARNING CYCLE DAN THINK TALK WRITE BERBANTUAN MEDIA AUDIOVISUAL - Sherly Anida Fahrina Putri; Wagiran Wagiran (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
The learning of news writing has not yet been implemented optimally, resulting in low academic scores for seventh-grade students. This condition is evident from the students' difficulties in independently developing ideas and in the writing process that adheres to the rules of news writing. The application of innovative learning models can encourage the effectiveness of learning to achieve optimal results. This study aims to examine the effectiveness of news writing instruction using the 5E Learning Cycle and Think Talk Write models, supported by the use of video-based audiovisual media, among seventh-grade students at MTs Negeri 1 Pati. This research employs a quantitative approach with a quasi-experimental design in the form of a nonequivalent control group design. Quantitative data was collected from the pre-test and post-test scores of news writing skills. Data analysis used descriptive analysis and a T-test. The results of the paired sample t-test for the experimental class and the control class obtained a sig. (2-tailed) value of 0.000 < 0.05, meaning there is a difference in learning outcomes. The results of the independent sample t-test obtained a sig. (2-tailed) value of 0.780 > table sig. 0.05, so there is no difference in news writing skills between the two groups. These findings indicate that the 5E Learning Cycle and Think Talk Write models, aided by audiovisual media, are effective in optimizing news writing learning because they result in significant differences in learning outcomes. However, the comparison test results of the two learning models show that there is no difference. This confirms that both models are equally effective when applied to teaching news writing. ABSTRAKPembelajaran menulis teks berita masih belum terlaksana secara optimal sehingga berdampak pada rendahnya nilai akademik peserta didik kelas VII. Kondisi tersebut terlihat dari kesulitan peserta didik dalam mengembangkan gagasan secara mandiri serta dalam proses penulisan yang sesuai dengan kaidah penulisan teks berita. Penerapan model pembelajaran yang inovatif mampu mendorong keefektifan pembelajaran agar dapat mencapai hasil yang optimal. Penelitian ini bertujuan mengkaji keefektifan pembelajaran menulis teks berita dengan penerapan model 5E Learning Cycle dan Think Talk Write yang didukung pemanfaatan media audiovisual berbasis video pada peserta didik kelas VII MTs Negeri 1 Pati. Penelitian ini menerapkan pendekatan kuantitatif dengan desain quasi eksperimental bentuk nonequivalent control group design. Data kuantitatif dikumpulkan dari nilai pretes dan postes keterampilan menulis teks berita. Analisis data menggunakan analisis deskriptif serta uji T. Hasil pengujian paired sample t-test kelas eksperimen dan kelas kontrol diperoleh nilai sig. (2-tailed) 0,000 < 0,05, artinya terdapat perbedaan terhadap hasil belajar. Hasil uji independent sample t-test diperoleh nilai sig. (2-tailed) 0,780 > sig. tabel 0,05, maka tidak terdapat perbedaan keterampilan menulis teks berita pada kedua kelompok. Temuan ini mengindikasikan bahwa model 5E Learning Cycle dan Think Talk Write berbantuan media audiovisual efektif dalam mengoptimalkan pembelajaran menulis teks berita karena memberikan perbedaan hasil belajar yang signifikan. Namun, hasil uji perbandingan kedua model pembelajaran menunjukkan bahwa tidak terdapat perbedaan. Hal ini menegaskan bahwa kedua model sama-sama efektif diterapkan dalam pembelajaran menulis teks berita.